Multimedia Boosts Fourth Graders' Reading Comprehension: Experimental Evidence: Meningkatkan Kemampuan Memahami Bacaan Siswa Kelas IV Melalui Multimedia Interaktif: Studi Eksperimental Kuantitatif - Weny Rahmawati; Kemil Wachidah (Universitas Muhammadiyah Sidoarjo, 2023)
This research aimed to investigate the impact of interactive multimedia on the reading comprehension skills of fourth-grade students at SDN Ketegan. The study involved 30 students and employed a one-group pretest-posttest design with a quantitative experimental approach. Data were collected through pre-test and post-test description questions. Statistical analysis revealed a significant improvement in students' reading comprehension skills, with a mean pretest score of 57.08 and a posttest score of 84.50. These findings indicate the positive influence of interactive multimedia on students' reading skills. The results emphasize the potential of interactive multimedia as an effective tool for enhancing reading comprehension abilities among elementary school students. Highlights: The study investigates the impact of interactive multimedia on reading comprehension skills of fourth-grade students. A quantitative experimental approach is used to gather data and analyze the results. The findings demonstrate a significant improvement in students' reading comprehension abilities after exposure to interactive multimedia. Keywords: Reading comprehension, Fourth grade students, Interactive multimedia, Quantitative experimental study, SDN Ketegan.